1963
DOI: 10.1037/h0042930
|View full text |Cite
|
Sign up to set email alerts
|

The orienting reflex as a function of the interstimulus interval of compound stimuli.

Abstract: The experiment investigated the orienting response as a function of temporal relations among the stimuli, with GSR the measure. 3 stimuli were employed. The duration of the 1st was 1300, 1050, or 750 msec., with 2 groups at each interval. The duration of the 2nd and 3rd were 600 and 100 msec., respectively. They terminated together and consisted of a tone and 2 different lights. Following 10 presentations of the compound, separate groups were tested to the 1st or 2nd stimulus alone. The shift from triple stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1966
1966
1982
1982

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Thompson and Spencer (1966) state that one of the nine parametric characteristics of habituation is that "habituation of response to a given stimulus exhibits stimulus gen-eralization to other stimuli." A large number of previous studies have shown that following habituation to one stimulus an intermodal or intramodal change in stimulus characteristics leads to increased responsiveness in adult humans (Allen, Hill, & Wickens, 1963;Badia & Defran, 1970;Coombs, 1938;Hare, 1968;Houck & Mefferd, 1969;Korn & Moyer, 1968;Weisbard & Graham, 1971;Zimmy, Pawlick, & Sour, 1969), human infants (Bernstein, Kessen, & Weiskopf, in press;Bridger, 1961), and other organisms (Bagshaw & Benzies, 1968;Bagshaw, Kimble, & Pribram, 1965;Peeke & Peeke, 1973). Although there is less abundant evidence that the amount of response increment is a function of the amount of difference between training and test stimuli, this relationship has now been demonstrated in several different organisms by using a variety of response measures (Apelbaum, Silva, Frick, & Segundo, 1960;Gorman, 1967;Engen & Lipsitt, 1965;Greer, 1969;Sokolov, 1963;Williams, 1963).…”
Section: Discussionmentioning
confidence: 99%
“…Thompson and Spencer (1966) state that one of the nine parametric characteristics of habituation is that "habituation of response to a given stimulus exhibits stimulus gen-eralization to other stimuli." A large number of previous studies have shown that following habituation to one stimulus an intermodal or intramodal change in stimulus characteristics leads to increased responsiveness in adult humans (Allen, Hill, & Wickens, 1963;Badia & Defran, 1970;Coombs, 1938;Hare, 1968;Houck & Mefferd, 1969;Korn & Moyer, 1968;Weisbard & Graham, 1971;Zimmy, Pawlick, & Sour, 1969), human infants (Bernstein, Kessen, & Weiskopf, in press;Bridger, 1961), and other organisms (Bagshaw & Benzies, 1968;Bagshaw, Kimble, & Pribram, 1965;Peeke & Peeke, 1973). Although there is less abundant evidence that the amount of response increment is a function of the amount of difference between training and test stimuli, this relationship has now been demonstrated in several different organisms by using a variety of response measures (Apelbaum, Silva, Frick, & Segundo, 1960;Gorman, 1967;Engen & Lipsitt, 1965;Greer, 1969;Sokolov, 1963;Williams, 1963).…”
Section: Discussionmentioning
confidence: 99%
“…In the case any "positive" results are open to the method-of the SSCE OR argument, it is interesting to note ological-confound version of the SSCE OR argu-that the evidence that has been adduced in its ment. Yet there is probably no issue which is more support has uniformly been used on conditioning critical to our theoretical understanding of SCR "analog" (Badia & Defran, 1970) situations where conditioning, since the short interval US-CS para-"surrogate" (Allen, Hill, & Wickens, 1963) rather digm is one where S-R contiguity-reinforcement than real USs are used. Yet when the identical theory (cf., e.g., Jones, 1962) and Russian positions "surrogate'' US arrangements (e.g., Furedy, 1969) (cf., Gormezano & Tait, 1976), predict excitatory yielded apparently contrary results to the argument, conditioning, most North American "pairings" the common reaction of referees and other propoanalyses predict no conditioning, and "contin-nents of the argument was that such conditioning gency" positions (cf., e.g., Rescorla, 1967) predict "analog" situations were not, after all, "relevant" inhibitory conditioning.…”
Section: Analytic Examination Of the Evidencementioning
confidence: 99%
“…The ISI pattern which is most common in conditioning and which has been examined from an OR point of view by other investigators (e.g., Allen, Hill, & Wickens, 1963;Stern, Das, Anderson, Biddy, & Surphlis, 1961) is the "forward" one where cs onset precedes ucs onset by a short time interval. The pattern which the present experiment sought to duplicate was a "backward" one, where the ucs-cs onset interval was 0.75 see.…”
mentioning
confidence: 99%